What Happens Stays - Annemarije Rus (Journal of Festive Studies)
Although celebration is a classic anthropological subject, little research has been done on party holidays. After high school graduation, Dutch youth head to Lloret de Mar in Spain for a party holiday to losgaan, or get loose. This term implies the breaking of boundaries, a sense of liberation and freedom. But to get loose, you need to hold on: to friends, a holiday lover, gender and nationality identifications, and to your phone. The visual ethnographic film titled Lloret ’18 invites you to question the freedom implied in nightlife, tag along with Dutch youth on their adventures and reflections, and consider the ways social media shapes our realities. This article considers the value of ethnographic filming in a party setting as well as the ethical issues that its practice raises. (Watch the film.)